The influence of visual elements of social media on the behavior of Generation Z tourists - Marić, Dražen (Naše gospodarstvo, 2025)
In today's online world, where all information is available to users with just one click, it is challenging to determine their credibility. Given the fact that there are almost 5 billion social media users, it is safe to say that social media has become an essential part of everyday life for many users, especially members of Generation Z. When filtering the pool of information, visual elements play a significant role in the decision-making process for users. Generation Z is composed of young people born between 1995 and 2005. They are considered the originators of social media and the virtual world, and spend the most time analysing content in the form of photographs or videos. The main reason why Generation Z members prioritise visual elements more than textual ones stems from the higher degree of reliability and trust that this type of content displays. To analyse how photos and videos influence the trust of members of Generation Z in online recommendations, a survey was conducted in the territory of the Republic of Serbia, in which the Pearson correlation test was applied. The research lasted from February to March 2024. Moreover, a study was conducted on a sample of 305 respondents, where the sample was convenience, and the obtained data were tested using the IBM SPSS Statistics platform. The main findings indicate how visual elements of social media, such as photos and videos, influence a greater degree of trust in credibility among Generation Z.
Keywords: eWOM (elektronsko ustno izročilo); generacija Z; odločanje; turizem; verodostojnost; vizualni elementi